The lesions of the velogenic newcastle disease virus infection in the lymphoid organs suppress antibody response to infectious bronchitis vaccination in La Sota vaccinated and unvaccinated chickens - Didacus Chukwuemeka Eze; Jacinta Ngozi Omeke; Amarachukwu Olejieme Igwe; Halima Idrisa Gambo; John Osita Arinze Okoye (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux)
Background: Velogenic Newcastle disease (vND) is a major disease of poultry worldwide. One of the common lesions of the disease is atrophy of the lymphoid organs. Aim: This project studied the ability of these lesions to suppress antibody response to infectious bronchitis (IB) vaccination in both chickens vaccinated and unvaccinated with the La Sota vaccine. Methods: One hundred fifty two-week-old cockerel chickens were divided into three groups, namely: a vaccinated challenged (VC) group, an unvaccinated challenged (UC) group, and an unvaccinated and unchallenged (UU) group. The VC group was given the La Sota vaccine at two weeks of age. At four weeks of age, all of the groups were challenged with the vND virus (vNDV). Results: Mortality was 82% in the UC group with lesions in the digestive and lymphoid organs. The VC group showed no clinical signs but there was severe atrophy and necrosis of the lymphoid organs. Fifteen chickens in the VC and UU groups and fifteen in the UC group were vaccinated with an infectious bronchitis vaccine at 14 and 28 days post challenge. After each vaccination, blood was collected from the chickens on days 7, 14, 21 and 28 post vaccination, and the sera were assayed for the IB antibody titers. The results showed that the titers in the UU chickens were significantly higher (p<0.05) than those in both the VC and UC chickens on nearly all of the days tested. Conclusions: The findings indicate that vNDV infection suppresses the antibody response to infectious bronchitis vaccination in both vaccinated and unvaccinated chickens.